Liquiritigenin promotes osteogenic differentiation and prevents bone loss via inducing auto-lysosomal degradation and inhibiting apoptosis - Yu Qiu; Yueyang Zhao; Zhimin Long; Aijia Song; Peng Huang; Kejian Wang; Ling Xu; David Paul Molloy; Guiqiong He (Genes and Diseases, 2023)
Osteoporosis (OP) is a debilitating skeletal abnormality involving bone remodeling and bone cell homeostasis characterized by decreased bone strength and high fracture risk. A novel therapeutic intervention for OP by manipulating cellular autophagy–apoptosis processes to promote skeletal homeostasis is presented. Protective effects of the naturally occurring plant extract Liquiritigenin (LG) were demonstrated in an ovariectomy (OVX)-OP mouse model and preosteoblast MC3T3-E1 cells. Micro-CT and histological staining assessments of skeletal phenotype were applied alongside detection of autophagy activity in osteocytes and MC3T3-E1 cells by transmission electron microscopy (TEM). The effects of LG on chloroquine (CQ)- and the apoptosis-inducing TS-treated osteogenic differentiations and status of lysosomes within MC3T3-E1 cells were analyzed by Neutral red, Alizarin red S and alkaline phosphatase (ALP) staining and Western blot assays. Treatment with LG prevented bone loss, increased osteogenic differentiation in vivo and in vitro, and inhibited osteoclast formation to some extent. TEM analyses revealed that LG can improve auto-lysosomal degradation within osteocytes from OVX mice and MC3T3-E1 cells. The abnormal status of lysosomes associated with CQ and TS treatments was notably alleviated by LG which also reduced levels of apoptosis-induced inhibition of osteogenic differentiation and averted abnormal osteogenic differentiation as a consequence of a blockage in autolysosome degradation. Overall, LG stimulates bone growth in OVX mice through increased osteogenic differentiation and regulation of autophagy-apoptosis mechanisms, presenting an auspicious natural therapy for OP.